تعليم النحو باستخدام كتاب "العمريطي" في مدرسة قاسم الهادى الثانوية ‏الإسلامية سمارانج ومشكلاته - Hilmi Sahab (LISANIA: Journal of Arabic Education and Literature, 2019)
This study aims to determine the process of implementing Nahwu learning with al Imrithi Books in schools that are integrated with Islamic boarding schools and find out about learning problems and analysis of solutions. This research was conducted in Qosim al Hadi high school Semarang. This type of research is field qualitative research by using: Observation, Interview, Documentation and Questionnaire as the technique of collecting data. The results of this study indicate that the learning method used in Nahwu's learning with al Imrithi Books is a Deductive method that is well known among boarding schools as a Bandongan method. This method is used to convey learning material, while the Sorogan method is a form of reinforcement of the material that has been studied. The learning problems in Nahwu's learning with the book al Imrithi from several aspects: Students, Teachers, Learning Materials, Learning Time and Institutional Foundations.